Environmental Conflict and Human Rights: Indigenous Peoples' Struggle Against Land Exploitation in Papua - Alexa Rimordiaz; Suswanta Suswanta (Jurnal Ilmu Sosial dan Humaniora, 2025)
Environmental conflict in Papua represents a complex intersection of land dispossession, ecological degradation, and the systemic violation of indigenous rights. While substantial research has addressed agrarian conflict in Papua, much of it remains concentrated on historical and structural dimensions particularly the legacy of colonialism in facilitating land exploitation. However, limited attention has been paid to how digital media frames these conflicts and the implications such portrayals have on public perception and the political agency of indigenous communities. This study fills that gap by analyzing how environmental conflicts in Papua are represented in online media and how these representations shape discourses around human rights and indigenous resistance. This research Using a qualitative content analysis, this research draws on secondary data from two major Indonesian news platforms, detik.com and kumparan.com, covering a specific period to ensure contextual relevance. The data comprising news reports, opinion pieces, and analytical articles were analyzed using NVivo 12 Plus to examine sentiment patterns, actor dynamics, and framing mechanisms. Social conflict theory and the principle of Free, Prior and Informed Consent (FPIC) were applied to interpret findings within a rights-based framework. Results reveal a dominant narrative centered on resource exploitation and indigenous opposition, with favorable framing of state and corporate actors and minimal attention given to indigenous perspectives. This framing bias obscures the structural roots of the conflict and undermines public understanding of its multidimensional nature. The study highlights the media’s dual role in shaping discourse and calls for more equitable communication strategies that affirm indigenous participatory rights within sustainable development agendas aligned with human rights and FPIC standards.